2019
DOI: 10.1128/mbio.00728-19
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Fungus Drives Nodulation and N 2 Fixation Attributable to Specific Root Exudates

Abstract: Endophytic fungi play important roles in the modification of ecosystem productivity; however, the underlying mechanisms are only partly understood. A 2-year field plot experiment verified that the endophytic fungus Phomopsis liquidambaris increased peanut (Arachis hypogaea L.) yields and significantly increased nodulation and N2 fixation regardless of whether N fertilizers were added. Root exudates collected from P. liquidambaris-colonized plants significantly improved nodulation and N2 fixation. Rhizosphere s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 66 publications
0
38
0
Order By: Relevance
“…The similar bacterial community compositions in rhizospheres of the treatments D1 and H3 (Figures 1, 2) might imply that similar root exudates were produced by soybean plants in these two treatments, since the rhizosphere microbiome was strongly regulated by root exudates (Haichar et al, 2008;Subbarao et al, 2009;Huang et al, 2014;White et al, 2015;Szoboszlay et al, 2016) and compounds sloughed off root tips (Bulgarelli et al, 2013), which could be related to N fertilization, colonization of endophytic microbe, and N 2 fixation of legume plant (Xie et al, 2019). To confirm this estimation, a comparative study on the root exudates is needed.…”
Section: Discussionmentioning
confidence: 98%
“…The similar bacterial community compositions in rhizospheres of the treatments D1 and H3 (Figures 1, 2) might imply that similar root exudates were produced by soybean plants in these two treatments, since the rhizosphere microbiome was strongly regulated by root exudates (Haichar et al, 2008;Subbarao et al, 2009;Huang et al, 2014;White et al, 2015;Szoboszlay et al, 2016) and compounds sloughed off root tips (Bulgarelli et al, 2013), which could be related to N fertilization, colonization of endophytic microbe, and N 2 fixation of legume plant (Xie et al, 2019). To confirm this estimation, a comparative study on the root exudates is needed.…”
Section: Discussionmentioning
confidence: 98%
“…Although some studies have reported that DSE can act as plant growth promoters (Zhu et al, 2015; He et al, 2019; Xie et al, 2019), their effects on plants are still limited under drought stress conditions (Li et al, 2018). The results of existing studies on the effects of inoculation of DSE on plant growth under water deficiency conditions are variable.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were performed with Ph. liquidambaris strain B3 and peanut-nodulating rhizobium, Bradyrhizobium yuanmingense (hereafter Bradyrhizobium) [8,22]. To mimic soil conditions, soil extraction agar (SEA, 1.5% agar) was used to activate Ph.…”
Section: Microorganisms and Growth Mediamentioning
confidence: 99%
“…Although no direct interactions between two root symbionts and concomitant effects on nodulation are known, Ph. liquidambaris inoculation increased bradyrhizobial diversity in peanut rhizosphere [22], suggesting the possible role of Ph. liquidambaris in rhizobial rhizosphere enrichment.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation